2016
DOI: 10.3389/fmicb.2016.00817
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MRSA Activities of Enterocins DD28 and DD93 and Evidences on Their Role in the Inhibition of Biofilm Formation

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) has become a worrisome superbug. This work aimed at studying the effects of two class IIb bacteriocins, enterocins DD28 and DD93 as anti-MRSA agents. Thus, these bacteriocins were purified, from the cultures supernatants of Enterococcus faecalis 28 and 93, using a simplified purification procedure consisting in a cation exchange chromatography and a reversed-phase high-performance liquid chromatography. The anti-Staphylococcal activity was shown in vitro by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…Nevertheless, it is worth mentioning that in this study we used enterocin without concentration or purification, we obtained promising results. Other studies have also reported the efficacy of unpurified enterocins against gram positive bacteria (CAMARGO et al 2016;AL ATYA et al 2016;ROCHA et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is worth mentioning that in this study we used enterocin without concentration or purification, we obtained promising results. Other studies have also reported the efficacy of unpurified enterocins against gram positive bacteria (CAMARGO et al 2016;AL ATYA et al 2016;ROCHA et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This attribute has been observed for example, in enterocin E-760 (Line et al, 2008 ), enterocin P (Cintas et al, 1997 ), enterocin LR/6 (Kumar and Srivastava, 2010 ), and Enterocin AS-48 (Cobo Molinos et al, 2008 ). Besides, enterocins DD28 and DD93 have been reported to be active against MRSA and prevented film formation (Al Atya et al, 2016 ). Similarly, strains E. durans 61A (Hanchi et al, 2016 ), E. mundtii ST15 (De Kwaadsteniet et al, 2005 ), and ST4SA (Dicks et al, 2010 ) have showed a broad spectrum of activity including Gram-negative bacteria, an unusual property of bacteriocins produced by LABs.…”
Section: Advantages Of Enterococci and Their Bacteriocinsmentioning
confidence: 99%
“…The enterocins were effective at inhibiting the formation of MRSA-1 biofilms on glass and SS surfaces when combined with the antibiotics kanamycin or erythromycin. 118 Finally, a novel circular sactibiotic, hyicin 4244, produced by Staphylococcus hyicus 4244, has been shown to exhibit anti-biofilm activity against fourteen Staphylococcus strains which were the causative agents of either bovine or human mastitis. 119 Significantly, the sactibiotic decreased the biofilm forming capacity of two of these strains as well as decreasing CFU (colony forming unit) counts.…”
Section: Anti-biofilm Activity Of Other Groups Of Bacteriocinsmentioning
confidence: 99%